PENERAPAN MODEL COOPERATIVE LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN PARTISIPASI MURID PADA MATA PELAJARAN PPKn KELAS X SMA ITP SURABAYA - Kusuma, Achmad Arif Rizal Ilham Putra; Wahyuni, Antin Tri; Caesa, Balqis Shabira Al-May; Laila, Fitriana Dewi Nur; Trianingsih, Mei Lantika; Syaidah, Rohmatus; Suhartono; Lidawati, Eka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila and Civic Education (PPKn) instruction for Grade X students at SMA ITP Surabaya remains dominated by conventional, teacher-centered methods, resulting in low levels of student collaboration. Students tend to be passive, reluctant to work in groups, dismissive of peers' opinions, and less responsible for shared tasks, hindering the internalization of democratic values. This study aimed to describe the implementation of two Cooperative Learning models—Gallery Walk and Teams Games Tournament (TGT)—and analyze their effects on students' collaborative attitudes in PPKn learning. The study employed a qualitative Classroom Action Research (CAR) design based on Djajadi's (2019) model, consisting of planning, implementation, observation, and reflection. The research involved 31 Grade X (Phase E) students (12 male and 19 female) and was conducted over three cycles. Gallery Walk was implemented in Cycle 1, while TGT was applied in Cycles 2 and 3. Data were collected through observations of students' collaborative behavior using a four-point rating scale, product assessments, tournament quizzes, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldana (2014). The findings revealed a consistent improvement in students' collaborative attitudes, with the mean score increasing from 80.97 in Cycle 1 to 90.87 in Cycle 2 and 91.32 in Cycle 3. The proportion of students in the